Neuroprotective Effect Of Andrographispaniculata In Betaamyloid Model Of Inflammation And Oxidative Stress - Khor, Boon Keat (2019)
The extracellular accumulation and deposition of P-amyloidi-42 (Ap) plaques in neuronal cells has been well accepted as one of the neuropathologic hallmarks of Alzheimer disease. This misfolded protein cause activation of glial cells and increase of reactive oxygen species (ROS) and inflammatory mediators in the brain, leading to neuronal dysfunction and death. Studies suggested that phytochemicals found in the plant may attenuate the toxicity and inflammation caused by Ap. In this study, the neuroprotective potential of Andrographis paniculata standardised extracts and its diterpenes was evaluated in the Ap model of inflammation and oxidative stress. Three extracts, namely aqueous [AP(H2O)]» 50% ethanolic (50% EtOH) and 95% ethanolic (95% EtOH) were prepared (yield of 25-30.5%) and standardised using the major diterpenes, andrographolide (ADG), neoandrographolide (Neo) and 14-deoxy- 11,12-didehydroandrographolide (AP3).